Pengaruh Slow Stroke Back Massage Terhadap Perubahan TingkatHipertensi di Desa Bengkaung Kecamatan Batulayar - Suhartiningsih; I Gusti Ayu Mirah Adhi; Nurhayati; Yusi Rizkianti (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Introduction: WHO data shows that around 1.13 billion or 22% of people suffer from hypertension out of the world's total population. In Indonesia, the number of hypertension sufferers in 2018 was 658,201, where the area with the highest number of hypertension cases was in Bengkaung Village with 268 respondents. Purpuse: This research is to determine the effect of slow Stroke Back Massage (SSBM) therapy on reducing blood pressure in patients with hypertension in Bengkaung Village, Batulayar District, West Lombok Regency. Methods: The design of this research is pre-experimental with a one group pre-test post-test design type. The population in this study was 268 people. Simple random sampling method, 31 people. Data analysis used the Wilcoxon signed rank test. Slow Stroke Back Massage therapy is given 3 times for 1 week for 3-10 minutes. Result: research shows that the majority of respondents were female, 20 respondents (65%). The age range of respondents is in the middle age 45-59. Blood pressure before being given slow stroke back massage therapy, most respondents experienced mild hypertension, 17 respondents (52.80%). The blood pressure results after being given slow stroke back massage therapy showed a decrease in blood pressure at a mild stage for 28 respondents (90.30%). Wilcoxon test results Decision making is based on the Wilcoxon Sig (2-tailed) statistical output < 0.05, which is worth 0.000, so it can be concluded that the hypothesis is accepted. Suggestion: programs at community health centers should provide slow stroke back massage therapy to hypertensive patients, as a complementary therapy.